Photothermal plasmonic microballs for non-contact single-cell calcium ionophore delivery in heterogeneous cells. Issue 2 (8th December 2022) - Ho, Vuong Thi Thanh Xuan; Song, Min Seok; Kim, Gun; Nguyen, Nguyen Binh; Dao, Thi Phuong; Lee, So Yeong; Joo, Sang-Woo
Abstract : Hierarchical plasmonic nanostructures comprising gold-nanorod-covered size-controlled microballs show good potential for selective delivery, as demonstrated by single-cell calcium ionophore transport and apoptosis induction. Abstract : Hierarchical plasmonic nanostructures comprising gold nanorod (AuNR)-covered microballs via syringe-injection reduction show good potential for selective single-cell calcium ionophore (A23187) delivery and apoptosis induction in heterogenous cancer cells.